A combined experimental and quantum chemical studies on the structure and binding preferences of picolinamide based ligands with uranyl nitrate. (1st October 2019) - Das, Debasish; Joshi, Meenakshi; Kannan, Shanmugaperumal; Kumar, Mukesh; Ghanty, Tapan K.; Vincent, Tessy; Manohar, Smitha; Kaushik, C.P.
Graphical abstract: Coordination chemistry of picolinamide based ligands with uranyl nitrate is studied through the synthesis and characterization of their complexes. The interesting matter here to be observed that only bidentate chelating type of bonding is observed in case of uranyl nitrate with the ligands under study although in previously reported complexes with some different metal ion, two types of bonding (monodentate and bidentate chelating) was observed with the same set of ligands. Here the alkyl groups attached with the amide N-atom didn't play any role to modulate the structure and bonding of the uranyl nitrate–ligand complexes. Abstract: Three N, N-substituted pyridine 2-carboxamide ligands, C5 H4 NCONRR′ (where, R, R′ = i C3 H7 (L 1 ); R, R′ = i C4 H9 (L 2 ); and R = H, R′ = t C4 H9 (L 3 ), as well as their coordination complexes (1 –3 ) of uranyl nitrate have been synthesized. All the ligands and their corresponding complexes were characterized by CHN elemental analysis, infrared (FTIR) and NMR spectroscopy. The crystal structure of the complex1 shows that the central uranium atom occupies a distorted hexagonal bipyramidal geometry, where the four oxygen atoms of the bidentate nitrate ligands with the oxygen and nitrogen atoms of the ligandL 1 form the hexagonal plane and two axial oxygen atoms of uranyl occupy the trans axial position. Here, the ligand acts as a bidentate chelating ligand. The preliminary structural analysis of the complex3 also indicates similar kind of structure as that of the complex1 . Quantum mechanical calculation at DFT level is supportive with the solid state structure obtained from X-ray crystallographic analysis.